2008
DOI: 10.1634/stemcells.2007-0891
|View full text |Cite
|
Sign up to set email alerts
|

Horizontal Basal Cells Are Multipotent Progenitors in Normal and Injured Adult Olfactory Epithelium

Abstract: The mammalian olfactory neuroepithelium provides a unique system for understanding the regulation of neurogenesis by adult neural stem cells. Recently, mouse horizontal basal cells (HBCs) were identified as stem cells that regenerate olfactory receptor neurons (ORNs) and nonneuronal cell types only after extensive injury of the olfactory epithelium (OE). Here we report a broader spectrum of action for these cells. We show that even during normal neuronal turnover, HBCs actively generate neuronal and non-neuron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
122
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(129 citation statements)
references
References 40 publications
5
122
0
2
Order By: Relevance
“…Recent studies of adult olfactory and oral mucosae reveal that the lamina propria within these tissues are a source of mesenchymal stem cells with extensive differentiation potential [24,[36][37][38]. The olfactory mucosa also contains neural stem cells, situated within the olfactory epithelium, maintaining a lifelong turnover of olfactory receptor neurons [39]. Our in vitro characterization of the olfactory stem cells used in this study suggests that these cells are mesenchymal stem cells.…”
Section: Discussionmentioning
confidence: 66%
“…Recent studies of adult olfactory and oral mucosae reveal that the lamina propria within these tissues are a source of mesenchymal stem cells with extensive differentiation potential [24,[36][37][38]. The olfactory mucosa also contains neural stem cells, situated within the olfactory epithelium, maintaining a lifelong turnover of olfactory receptor neurons [39]. Our in vitro characterization of the olfactory stem cells used in this study suggests that these cells are mesenchymal stem cells.…”
Section: Discussionmentioning
confidence: 66%
“…One study that traced HBC lineage after injury reported that HBCs remain dormant after the selective loss of mature neurons that follows olfactory bulbectomy (OBX) (9). However, the same kind of injury produced a different result in animals bearing a leaky RU486-responsive CrePR transgene driven by a Krt5 promoter (12). In the latter paradigm, some HBCs were apparently activated to multipotency following OBX.…”
Section: Resultsmentioning
confidence: 99%
“…However, as a consequence of severe tissue injury and the wholesale loss of both neurons and sustentacular (Sus) cells, HBCs lose their attachment to the basal lamina, proliferate, transition into GBCs, and give rise to all types of cellular constituents of the OE during its regeneration, a constellation of responses that we term "activation" (9)(10)(11). In contrast, existing data suggest that selective neuronal loss in response to ablation of the olfactory bulb does not result in HBC activation (9), although another laboratory has observed an enhanced HBC contribution to the epithelium after bulb ablation (12). The effect of the targeted death of Sus cells has not been investigated.…”
mentioning
confidence: 94%
“…HBCs express the epithelial markers keratin 5 (K5) and CD54 (also known as ICAM-1), and HBCs express the stem cell markers Pax6 and Sox2 [5][6][7][8]. Although the evidence collected to date is far from conclusive, it has been suggested that HBCs are the tissue stem cells in the OE because HBCs can self-renew and generate neuronal and non-neuronal cells, including the GBCs, in vivo (both during normal turnover and following OE injury) as well as in vitro [4,[9][10][11]. HBCs express the transcription factor p63, which is essential for the proliferation of epithelial stem cells that give rise to the thymus and epidermis [12].…”
Section: Introductionmentioning
confidence: 99%